(untitled) (Texas Journal of Medical Science, 2024)
Our research was conducted at the multidisciplinary clinic of the Tashkent Medical Academy.Clinical functional changes were conducted among 46 patients with bronchial asthma.The average duration of the disease is 24,2 years.When we analyzed the patients with bronchial asthma, the degree of clinical functional changes in patients increased with the increase of disease. Indicators of obstructive disorders a significant decrease in peak expiratory flow rate ( PEFR) up to 55,6±6.9% and Lung capacities up to 69.7±6.4% confirms the nature of clinical signs and obstructive disorders.PEFR showed a significant decrease from 78% to 35% with the severity of the disease stage in BA patients and an increase in clinical symptoms depending on the level of the disease